Design and validation of an instrument to assess health and work conditions of physical therapists in Colombia (2016)
Introduction: The national survey on health and work conditions of physiotherapists did not have designed and validated instruments that considered the broad analytical framework of the relationship between health and work. Objective: To present construction and validation processes of the instrument known as health conditions and physical therapists work in Colombia. Materials and methods: Cronbach’s alpha coefficient was used to measure the relationship between responses to each variable and the magnitude of each category, establishing fixed and consistent measurements with a high level of correlation. The validation process was carried out with 1 711 Colombian physiotherapists, graduated between 1980 and 2012. Results: The assessment of internal consistency through Cronbach’s found five highly coherent categories, three values greater than 0.8 (hazardous working conditions, organization of work, job satisfaction), and two above 0.9 (events in health and disease and identity and autonomy). Discussion: The design and construction of the instrument for assessing health and work conditions of physiotherapists are generated based on the needs of physiotherapists to establish broad baselines regarding the relationship between work and health, and to understand working conditions as a structuring element of health and disease. © 2016, Universidad Nacional de Colombia. All rights reserved.